Catastrophic Kawasaki disease unresponsive to IVIG in a 3-month-old infant : a diagnostic and therapeutic challenge - Magalhães, Cristina Medeiros Ribeiro de (2012)
The present report describes the severe evolution of Kawasaki disease in a three-month-old infant. The ailment was initially atypical in its presentation, with the patient exhibiting only persistent fever in association with a progressive lethargy and maculopapular rash on the face, trunk and limbs erroneously diagnosed as roseola infantum. On the 10th day of the condition, mainly due to the unexplained persistence of fever, the infant was admitted to a local hospital. The typical features of KD appeared only on the 14th day of illness with the relapse of the maculopapular rash in association with non-purulent conjunctivitis; dry, reddish and fissured lips; tongue with reddish and hypertrophic papillae; erythema and edema of the palms and soles. During the following days, the ailment rapidly evolved to a catastrophic clinical picture characterized by generalized vasculitis, splenic infarction, pulmonary thrombosis, giant right and left coronary aneurysms, dilatation of common and internal iliac arteries and progressive ischemia of the distal third of the feet resulting in necrotic lesions of both halluces. Appropriate therapy was initiated, but repeated administration of intravenous immunoglobulin G (IVIG) followed by three days of administration of methylprednisolone did not abate the intense inflammatory activity. The remission of inflammation and regression of vascular lesions were only achieved during the following five weeks after the introduction of methotrexate associated with etanercept. The report of this case aims to draw attention to severe forms of KD that exhibit an unfavorable evolution and can be extremely refractory to the conventional therapy.